2015
DOI: 10.1016/j.jcrs.2014.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of opacified silicone intraocular lenses in patients with asteroid hyalosis

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 15 publications
0
17
0
2
Order By: Relevance
“…In patients with asteroid hyalosis, and who have had cataract surgery with implantation of a silicone IOL, whitish-gray deposits with a granular texture can accumulate as a crust-like layer on the posterior surface of the lens. 6 This material has been identified to be hydroxyapatite, consisting of calcium and phosphate. 1 , 2 It is believed to either be derived from the asteroid bodies or from a similar process that resulted in the vitreous condition itself.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients with asteroid hyalosis, and who have had cataract surgery with implantation of a silicone IOL, whitish-gray deposits with a granular texture can accumulate as a crust-like layer on the posterior surface of the lens. 6 This material has been identified to be hydroxyapatite, consisting of calcium and phosphate. 1 , 2 It is believed to either be derived from the asteroid bodies or from a similar process that resulted in the vitreous condition itself.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ophthalmologists might consider deferring laser posterior capsulotomy treatment in a suspected calcified silicone IOL to facilitate an IOL exchange procedure. 6 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asteroid hyalosis is characterized by bright asteroid bodies floating in the vitreous body. [6] Its prevalence is approximately 1% and increases with aging. [8] Analysis of the asteroid bodies demonstrated that calcium and phosphorus were its main components.…”
Section: Discussionmentioning
confidence: 99%
“…[1234] The opacification is characterized by progressive accumulation of white granular or fleck-like deposits that is localized to the posterior optic surface of the silicone IOL. [5] Although removal the calcification deposits using neodymium:yttrium–aluminum–garnet (Nd:YAG) laser is simple and safe, attempts to use Nd:YAG laser treatment have often been associated with unsatisfactory results or immediate re-accumulation of the deposits on the posterior surface of the IOL[126] IOL exchange have been considered the definitive treatment for the silicone IOL opacification. [1467] However, the method is technically difficult and associated with increased risk of complications.…”
Section: Introductionmentioning
confidence: 99%